Optimalisasi Kompetensi Guru dalam Identifikasi Siswa Tunarungu pada Sekolah Inklusif - Mursita, Rohmah Ageng; Winarsih, Murni; Bintoro, Totok; Manar, Mayasari; Herdiani, Wahyu (Forum Kerjasama Pendidikan Tinggi, 2025)
Inclusive education seeks to ensure equitable access to quality education for all children, including those with special needs. In practice, numerous educators in inclusive schools in Bekasi City face challenges in recognising and instructing children with hearing impairments. This study aims to evaluate the effectiveness of training provided to educators in enhancing their ability to identify and teach children with hearing impairments. The employed methodology is qualitative, utilising in-depth interviews, direct observations, and questionnaires. Data were gathered from 50 educators throughout 50 inclusive schools in Bekasi City. The study’s results indicate that the training effectively enhanced teachers’ proficiency in understanding the characteristics of deaf children and applying instructional approaches that utilise visuals, sign language, and auditory technology. The mean enhancement in teachers’ proficiency attained 30–35% across several domains, despite ongoing constraints associated with inadequate facilities and insufficient time for parental engagement. The findings indicate that extensive and continuous training is crucial for creating an improved, inclusive educational environment. It is essential to enhance collaboration among educators, parents, and other stakeholders to elevate the quality of inclusive education in Bekasi City.